Optimization of a Self-microemulsifying Drug Delivery System for Oral Administration of the Lipophilic Drug, Resveratrol: Enhanced Intestinal Permeability in Rat - Shahla Mirzaeei; Negar Tahmasebi; Ziba Islambulchilar (Tabriz University of Medical Sciences, 2023)
Purpose: This study aimed to formulate Resveratrol, a practically water-insoluble antioxidant in a self-microemulsifying drug delivery system (SMEDDS) to improve the solubility, release rate, and intestinal permeability of the drug. Methods: The suitable oil, surfactant, and co-surfactant were chosen according to the drug solubility study. Utilizing the design of experiment (DoE) method, the pseudo-ternary phase diagram was plotted based on the droplet size. In vitro dissolution study and the single-pass intestinal perfusion were performed for the investigation of in vitro and in-situ permeability for drugs formulated as SMEDDS in rat intestine using High-Performance Liquid Chromatography. Results: Castor oil, Cremophor RH60, and PEG 1500 were selected as oil, surfactant, and co-surfactant. According to the pseudo-ternary phase diagram, nine formulations developed microemulsions with sizes ranging between 145-967 nm. Formulations passed the centrifuge and freeze-thaw stability tests. The optimum formulation possessed an almost 2.5-fold higher cumulative percentage of in vitro released resveratrol, in comparison to resveratrol aqueous suspension within 120 minutes. The results of the in-situ permeability study suggested a 2.6-fold higher intestinal permeability for optimum formulation than that of the resveratrol suspension. Conclusions: SMEDDS can be considered suitable for the oral delivery of resveratrol according to the observed increased intestinal permeability, which could consequently enhance the bioavailability and therapeutic efficacy of the drug.